Analisis Persediaan dan Inventory Control Bahan Baku Garam Menggunakan Metode EOQ pada PT.MNO Sidoarjo - Annandita, Alifia Rizky; Winursito, Yekti Condro (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Demand is an asset whose value fluctuates. The number of requests can increase or decrease according to consumer wishes. To overcome this fluctuatuing demand, appropriate supplies of raw materials are maintained. Therefore, to calculate inventory can use the EOQ method. PT. MNO is company that operates in marine products. In dealing with raw material supplies, PT.MNO still uses old calculation methods. This research aims to analyze the optimal number of order, the amount of safety stock, reorder points, and compare the costs incurred by the company with the costs calculated based on the EOQ method. The type of research used primary data obtained through field observations. Based on the research results, the costs calculated based on EOQ are lower than the costs incurred by the previous company, in 2022 is Rp. 622.410 and 2023 is Rp. 352.868.